2020
DOI: 10.1523/jneurosci.0216-20.2020
|View full text |Cite
|
Sign up to set email alerts
|

Pupil Diameter Tracks Statistical Structure in the Environment to Increase Visual Sensitivity

Abstract: Pupil diameter determines how much light hits the retina and, thus, how much information is available for visual processing. This is regulated by a brainstem reflex pathway. Here, we investigate whether this pathway is under the control of internal models about the environment. This would allow adjusting pupil dynamics to environmental statistics to augment information transmission. We present image sequences containing internal temporal structure to humans of either sex and male macaque monkeys. We then measu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
48
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(56 citation statements)
references
References 53 publications
2
48
1
Order By: Relevance
“…Previous studies have shown that associative learning of face pairs does not lead to awareness of these associations 29 and that memory guidance occurs in the absence of explicit memory about the associations that form the basis of this guidance 14 . Similarly, we found that subjects were not better than chance in their explicit judgement whether two faces formed a pair when they actually did (mean difference − 3.68%, t (29) = − 1.44, p = 0.1606, g = − 0.2629).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that associative learning of face pairs does not lead to awareness of these associations 29 and that memory guidance occurs in the absence of explicit memory about the associations that form the basis of this guidance 14 . Similarly, we found that subjects were not better than chance in their explicit judgement whether two faces formed a pair when they actually did (mean difference − 3.68%, t (29) = − 1.44, p = 0.1606, g = − 0.2629).…”
Section: Resultsmentioning
confidence: 99%
“…Together, these findings suggest that pupil size reliably varies with the sudden changes in the environment's causal statistical structure. Schwiedrzik and Sudmann (2020) also highlight the critical finding that pupil dynamics adjust to the environment's temporal regularities. However, the way statistical regularities impact pupillary changes lacks consistency.…”
mentioning
confidence: 89%
“…In a recent study, Schwiedrzik and Sudmann (2020) demonstrated that the brainstem PLR pathway that accounts for pupil dynamics adjustment is controlled by the environment's internal models derived from higher-order temporal statistics. Pupil recordings of humans and monkeys were made as they viewed faces with and without statistical regularities, referred to as random and structured streams of faces, respectively.…”
mentioning
confidence: 99%
See 2 more Smart Citations